A educação ambientada no campo: uma revisão integrativa da literatura sobre a educação ambiental presente nos assentamentos rurais brasileiros - Luz, Guilherme José da (Universidade Federal de São Carlos, 2024)
Rural education is an empowering and motivating instrument for the rural population, as it allows, through teaching-learning, the development of local students and teachers based on pedagogical methodologies aimed at that reality. It is important that during teaching, the objectives of the rural environment and the origin of the place in which the school is located are considered, so that the formation of this community is aligned with the purposes and makes sense with the present legacy. Thinking about rural settlements, contact with the environment is very common in the settlers' daily lives. This interaction is relevant when we think about ways to combine the objectives of a rural school with the dynamics of the settlement. Environmental education emerges as a possible tool, given its transformative role and the possibility of critical development of society in relation to the environment. The present work seeks to understand how this interaction between environmental education and Brazilian rural settlements happens. To this end, an integrative literature review was carried out to understand this issue. Based on the twenty-six works reviewed, environmental education has a transformative role for settlers, settlements, researchers and organizations involved in the processes. These changes permeate several themes such as: social transformation; solid waste management; rural education; child education; environmental restoration; reduction of harm to health, among others. However, from the review it was understood that there is a need for more studies on this interaction, and for more resources to be invested in both research and settlements so that this relationship prospers even more in the future.
Education set in the countryside: an integrative review of the literature on environmental education present in brazilian rural settlements
Keywords: Educação do campo; Comunidades rurais; Bibliografia; Countryside education; Rural communities; Bibliography; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS HUMANAS::EDUCACAO